Hi-Res! : Amantes sunt Amentes. (Berlin : Gestalten, 2007)
The London-based design studio Hi-ReS! (Handsome information - Radical entertainment Systems!) was founded by Alexandra Jugovic and Florian Schmitt in 1999. Over the last years, Hi-ReS! has established itself as one of the leading studios worldwide in the realization and implementation of sophisticated interactive commercial projects. This book with DVD is the first to present a scintillating collection of projects by Hi-ReS! for a wide range of clients - from companies such as MTV, Diesel, Sony, Toyota and Nokia to musicians such as Beck and Massive Attack. The publication also includes moving and still images of some of the original websites and motion graphics Hi-ReS! created for TV programs like "Ugly Betty" and feature films like "Donnie Darko" and "Minority Report". The selection is rounded out by examples of their non-commercial pieces and installations. The strength of Hi-ReS! lies not only in its masterful linear storytelling, but also in its creation of sensual interactive experiences that pair an artistic, tongue-in-cheek approach with strong marketing sensibilities. As the work in this book with DVD shows, it's a combination that allows the studio to meet client goals while remaining true to the pioneering spirit of the online world. For its unique work, which mixes concepts, techniques and a generous portion of digital magic into new forms that delight the senses, Hi-ReS! has won professional and popular awards and accolades on both sides of the Atlantic. These include Clios, Golden Cyberlions, Webby Awards, a BAFTA and two Prix Ars Electronica.